Integrating a constraint-based optimization approach into the design of oil & gas structures. (August 2020) - Cicconi, Paolo; Nardelli, Miriam; Raffaeli, Roberto; Germani, Michele
Abstract: Currently, design optimization is widely applied in civil and mechanical engineering. Optimization strategies are used to enhance the product performance and reduce the cost, lead time and environmental impacts related to the product lifecycle. In this context, evolutionary algorithms are used for determining the optimum solution in engineering problems. The design of complex products, such as those that are engineered to order, often requires the study of subproblems. Modularization is a common practice to reduce the complexity; however, the configuration practices are difficult to be applied in engineered to order products. As a solution, the integration of the optimization tools and model-based simulations is proposed to manage the complexity. However, even when a commercial software is available to support the parameter optimization, there may exist a lack of design tools that can be integrated with the product structure of an engineered to order product. This paper describes a design optimization approach that integrates a Constraint Satisfaction Problem (CSP) tool with model-based simulations in a collaborative design context. A platform tool is developed using the .NET and MiniZinc languages. The case study is focused on the design optimization of a 700-ton steel structure. In particular, the optimization analysis considers the mechanical behavior, weight, and cost reduction.